Complicit fictions : the subject in the modern Japanese prose narrative - Fujii, James A. (Twentieth-century Japan ;, 1993)
In Complicit Fictions, James Fujii challenges traditional approaches to the study of Japanese narratives and Japanese culture in general. He employs current Western literary-critical theory to reveal the social and political contest inherent in modern Japanese literature and also confronts recent breakthroughs in literary studies coming out of Japan. The result is a major work that explicitly questions the eurocentric dimensions of our conception of modernity.